Does psychological intervention help chronic skin conditions? - Capoore, H. S. (BMJ Group, 1998)
The objective of the study was to assess the impact of psychological/psychiatric assessment in patients with chronic or intractable dermatological conditions. A diagnostic interview was undertaken in order to pin-point any temporal connection between an adverse life-event and the first appearance of the skin disorder. Following this, the dermatologist's assessment of subsequent changes in the skin disorder were noted. The three main dermatological diagnoses were atopic eczema (10), prurigo (10), and psoriasis (nine). Follow-up was for up to 5 years. A favourable response was noted in 40 out of the 64 patients who participated in the study; this was usually evident within a few weeks and maintained thereafter. Remission was achieved in 12, while 28 showed some improvement. We conclude that this liaison between dermatology and psychiatry proved a valuable adjunct to normal dermatological treatment and was followed by improvement in the majority of patients.